The world that we knew / [large type] - Hoffman, Alice (Center Point Large Print, 2019)
In Berlin, at the time when the world changed, Hanni Kohn knows she must send her twelve-year-old daughter away to save her from the Nazi regime. She finds her way to a renowned rabbi, but it's his daughter, Ettie, who offers hope of salvation when she creates a mystical Jewish creature, a rare and unusual golem, who is sworn to protect Lea. Once Ava is brought to life, she and Lea and Ettie become eternally entwined, their paths fated to cross, their fortunes linked. Lea and Ava travel from Paris, where Lea meets her soulmate, to a convent in western France known for its silver roses; from a school in a mountaintop village where three thousand Jews were saved. Meanwhile, Ettie is in hiding, waiting to become the fighter she's destined to be.